Robert Louis Stevenson : writer of boundaries - Ambrosini, Richard; Dury, Richard (University of Wisconsin Press, 2006)
Robert Louis Stevenson: Writer of Boundaries reinstates Stevenson at the center of critical debate and demonstrates the sophistication of his writings and the present relevance of his kaleidoscopic achievements. While most young readers know Robert Louis Stevenson (1850-1894) as the author of Treasure Island, few people outside of academia are aware of the breadth of his literary output. The contributors to Robert Louis Stevenson: Writer of Boundaries look, with varied critical approaches, at the whole range of his literary production and unite to confer scholarly legitimacy on this enormously influential writer who has been neglected by critics. As the editors point out in their Introduction, Stevenson reinvented the "personal essay" and the "walking tour essay," in texts of ironic stylistic brilliance that broke completely with Victorian moralism. His first full-length work of fiction, Treasure Island, provocatively combined a popular genre (subverting its imperialist ideology) with a self-conscious literary approach. Stevenson, one of Scotland's most prolific writers, was very effectively excluded from the canon by his twentieth-century successors and rejected by Anglo-American Modernist writers and critics for his play with popular genres and for his non-serious metaliterary brilliance. While Stevenson's critical recognition has been slowly increasing, there have been far fewer published single-volume studies of his works than those of his contemporaries, Henry James and Joseph Conrad.--Publisher description